Early detection of antiangiogenic treatment responses in a mouse xenograft tumor model using quantitative perfusion MRI. (6th January 2014) - Rajendran, Reshmi; Huang, Wei; Tang, Annie Mei Yee; Liang, Jie Ming; Choo, Stephanie; Reese, Torsten; Hentze, Hannes; van Boxtel, Susan; Cliffe, Adam; Rogers, Keith; Henry, Brian; Chuang, Kai Hsiang
Abstract: Angiogenesis plays a major role in tumor growth and metastasis, with tumor perfusion regarded as a marker for angiogenesis. To evaluate antiangiogenic treatment response in vivo, we investigated arterial spin labeling (ASL) magnetic resonance imaging (MRI) to measure tumor perfusion quantitatively. Chronic and 24‐h acute treatment responses to bevacizumab were assessed by ASL and dynamic‐contrast‐enhanced (DCE) MRI in the A498 xenograft mouse model. After the MRI, tumor vasculature was assessed by CD34 staining. After 39 days of chronic treatment, tumor perfusion decreased to 44.8 ± 16.1 mL/100 g/min ( P  < 0.05), compared to 92.6 ± 42.9 mL/100 g/min in the control group. In the acute treatment study, tumor perfusion in the treated group decreased from 107.2 ± 32.7 to 73.7 ± 27.8 mL/100 g/min ( P  < 0.01; two‐way analysis of variance), as well as compared with control group post dosing. A significant reduction in vessel density and vessel size was observed after the chronic treatment, while only vessel size was reduced 24 h after acute treatment. The tumor perfusion correlated with vessel size ( r  = 0.66; P  < 0.005) after chronic, but not after acute treatment. The results from DCE‐MRI also detected a significant change between treated and control groups in both chronic and acute treatment studies, but not between 0 and 24 h in the acute treatment group. These results indicate that tumor perfusion measured by MRI can detect early vascular responses to antiangiogenic treatment. With its noninvasive and quantitative nature, ASL MRI would be valuable for longitudinal assessment of tumor perfusion and in translation from animal models to human. Abstract : Tumor angiogenesis provides essential functional information for diagnosis and prognosis and tumor perfusion is regarded as a marker for angiogenesis. We investigated a noninvasive technique, arterial spin labeling (ASL) MRI, to measure tumor perfusion quantitatively. Our results indicate that tumor perfusion measured by ASL can detect early vascular responses, confirmed by histology, to treatment.